Ocorrência de aflatoxinas em castanhas do Pará (Bertholletia excelsa, Humb. & Bonpl., 1808) - Castrillón, Aurélia Lopes; Purchio, Adhemar (Acta Amazonica, 1988)
The occurrence of aflatoxins was investigated in one hundred samples of Brazil nuts (Bertholletia excelsa Humb. & Bonpl.) from producers and from several seed marketing posts, in the region of Manaus, State of Amazonas and São Paulo, state of São Paulo. The samples were classified according to four types of product presentation: naturally within the shell; dehydrated within the shell; dehydrated without shell and within the chestnut bur. Three samples were found contaminated with aflatoxins types B1 and G1. The toxicity levels for B1 were regarded as: medium (0,1 ppm) and very high (2.25 ppm); those ofaGI were regarded low (0.075) and very high (1.5 ppm).